COVID-19 and Ventilation in the Home; Investigating Peoples' Perceptions and Self-Reported Behaviour (the COVID-19 Rapid Survey of Adherence to Interventions and Responses [CORSAIR] Study). (May 2021) - Smith, Louise E; Potts, Henry WW; Amlȏt, Richard; Fear, Nicola T; Michie, Susan; Rubin, G James
Ventilating indoor spaces helps prevent COVID-19 transmission. We investigated self-reported rates of opening windows to improve ventilation in the home, perceived effectiveness of opening windows, and confidence that if you wanted to, you could open windows. One in 6 people reported rarely, if ever, opening windows in their home in the last week. Three in 4 people knew that opening windows to improve ventilation was an effective way to prevent the spread of COVID-19 and 5 in 6 were confident that they could open windows in their home. Official messaging should continue to seek to improve knowledge about the effectiveness of ventilation for reducing COVID-19 transmission, and increase the frequency of window opening.